2021
DOI: 10.1038/s41598-021-94035-5
|View full text |Cite|
|
Sign up to set email alerts
|

Combined prognostic nutritional index and albumin-bilirubin grade to predict the postoperative prognosis of HBV-associated hepatocellular carcinoma patients

Abstract: This study aims to evaluate the predictive value of the prognostic nutritional index (PNI) and albumin-bilirubin grade (ALBI) for the postoperative prognosis of hepatitis B virus-associated hepatocellular carcinoma (HBV-HCC) patients undergoing radical hepatectomy (RH). Besides, we seek to identify novel prognosis indicators for HBV-HCC patients. Between April 2009 and March 2015, this work enrolled 868 patients diagnosed with HBV-HCC and undergoing RH in the Liver Surgery Department, West China Hospital, Sich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It can be affirmed that albumin levels are determinant as a prognostic factor in patients with HCC. Low levels of serum albumin are associated with poor nutritional status and a worse prognosis at the diagnosis of HCC [48,49]. Furthermore, various studies describe the importance of albumin as a negative regulator in the progression of HCC, particularly in local invasion and metastasis of HCC [50].…”
Section: Discussionmentioning
confidence: 99%
“…It can be affirmed that albumin levels are determinant as a prognostic factor in patients with HCC. Low levels of serum albumin are associated with poor nutritional status and a worse prognosis at the diagnosis of HCC [48,49]. Furthermore, various studies describe the importance of albumin as a negative regulator in the progression of HCC, particularly in local invasion and metastasis of HCC [50].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective clinical studies have identified malnutrition as an independent negative prognostic factor in patients with HCC ( 26 ). Preoperative malnutrition may lead to increased postoperative infection and complications, resulting in delayed recovery ( 27 ). The predictive role of inflammation and nutrition markers in the prognosis of patients with HCC is of increasing interest.…”
Section: Discussionmentioning
confidence: 99%
“…HBV-HCC prognosis is linked to several factors, including tumor burden, AFP, disease stage, ALBI, and NLR (18,19), and there are also nomograms about HBV-HCC (20)(21)(22). However, no nomogram for HCC patients with high HBsAg expression after local treatment has been available to our knowledge.…”
Section: Introductionmentioning
confidence: 99%